Otaku Subculture Character in Japanese Poetry Anthology Otaku Senryu - Indah Fitriani; Lina Meilinawati; N. Rinaju Purnomowulan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This paper focuses on one the subcultures existing in Japan, known as otaku. Subculture is a forum for youth community media and technology enthusiasts, like manga (Japanese comics), anime (Japanese cartoons), video games, computers, and the Internet. In the process, otaku who initially labeled negatively has contributed significantly to Japan as the most advanced industrialized country in Asia, not only in the field of culture, but also in the fields of science and economics. Using data from Japanese poem anthology (senryu) in Otaku Senryu(OS), this paper focuses on 1) distinctiveness of otaku character and; 2) factors supporting construction of otaku’s character. The method applies Riffaterre’s semiotic approach. The result obtained is that the otaku distinctiveness lies in their tendency to not be able to escape media and technology. Media and technology have transformed them into a difficult person in interacting and communicating directly with others as they have become introverted, obsessive, and also consumptive.